Agency theory: background and epistemology. Issue 4 (12th September 2016) - Bendickson, Josh; Muldoon, Jeff; Liguori, Eric W.; Davis, Phillip E.
Abstract : Purpose: By revisiting the agency theory literature, this paper aims to both incrementally advance historical viewpoints and reveal four prominent influences on agency theory: Weber and Simon, The Great Depression, Cooperation and the Chicago School. This is critical given that understanding the history behind the authors' major theoretical lenses is fundamental to using these theories to explain various phenomena. Design/methodology/approach: Drawing on a plethora of archival sources and following the influence-mapping approach used by other management history scholars, this manuscript synthesizes historical accounts and archival information to provide a clearer picture of the major historical influences in the formation of agency theory. Findings: We shed light on four areas related to management history that helped propel agency theory. Whereas past scholarship has not recognised them as influencers, we find and show how the industrial revolution, unionization, the stock exchange and other management approaches all played a role in the development of agency theory's core tenants. Originality/value: We extend upon the influential people and events that shaped agency theory, thus providing a fuller understanding of the theory's usefulness. Moreover, we fill in gaps enabling scholars to better understand the context in which the core tenants of agency theory were developed.